2015
DOI: 10.1016/j.ajpath.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Receptor Antagonism Enhances Proliferation and Migration of Engrafted Neural Progenitor Cells in a Model of Viral-Induced Demyelination

Abstract: The oral drug FTY720 affects sphingosine-1-phosphate (S1P) signaling on targeted cells that bear the S1P receptors S1P1, S1P3, S1P4, and S1P5. We examined the effect of FTY720 treatment on the biology of mouse neural progenitor cells (NPCs) after transplantation in a viral model of demyelination. Intracerebral infection with the neurotropic JHM strain of mouse hepatitis virus (JHMV) resulted in an acute encephalomyelitis, followed by demyelination similar in pathology to the human demyelinating disease, multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 63 publications
(69 reference statements)
3
35
0
Order By: Relevance
“…However, we failed to observe similar results in cultured NSCs, as no significant differences were found among groups of β -tubulin III positive cells. Our conclusion was supported by a study on a viral-induced demyelination mice model [16]. And no neuron differentiation on embryonic hippocampal NSCs has also been reported recently [25].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, we failed to observe similar results in cultured NSCs, as no significant differences were found among groups of β -tubulin III positive cells. Our conclusion was supported by a study on a viral-induced demyelination mice model [16]. And no neuron differentiation on embryonic hippocampal NSCs has also been reported recently [25].…”
Section: Discussionsupporting
confidence: 83%
“…However, more morphological matured oligodendrocytes were seen in the higher dose FTY720 groups. The different results among groups might be because of people using different originated NSCs or diseases models [1, 16, 2931]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all experimental groups, the g ratios averaged ϳ0.8, indicating normal myelinated axons in the spinal cord ( Fig. 3E and F) (55)(56)(57). These findings argue that inducible deletion of CXCR2 in oligodendroglia lineage cells in young (4-week-old) mice does not affect the myelin content in a nondisease state.…”
mentioning
confidence: 65%
“…Our findings are consistent with those of Kerstetter et al (58), who showed that treatment of mice with MOG 35-55 -induced EAE with small-molecule antagonists specific for CXCR2 resulted in improved motor skills that correlated with diminished white matter damage associated with enhanced re-myelination, arguing that CXCR2 may be a relevant therapeutic target for the treatment combination with Luxol fast blue (LFB), and between 4 and 8 sections per mouse were analyzed. Areas of total white matter and demyelinated white matter were determined with ImageJ software, and demyelination was scored as the percentage of total demyelination from the spinal cord sections analyzed (55,67,70).…”
Section: Discussionmentioning
confidence: 99%